Interlinkages Between Indian and Global Stock Market Returns : Evidence from G5 Countries - Gawade, Sushma; Parab, Narayan; Reddy, Y. V. (Indian Journal of Finance, 2019)
Globalization has brought the world nations together with respect to trade and strategic alliances. The present study focused on investigating interlinkages between Indian and global stock markets. For this purpose, a group of five budding countries of the 21st century was selected, that is, Brazil, China, India, Mexico, and South Africa, also known as G5. Considering a data from 2001 to 2017, the study attempted to examine the relationship, causality, and impact between Indian and global stock market returns. The results indicated a strong positive relationship between Indian and global stock market returns, and such relation was found to be highest with the Shanghai Composite Index returns (China). The study also evidenced bidirectional causality between Indian and global stock market returns. Also, a significant positive impact of global stock market returns was noticed. The results will be helpful for investors belonging to G5 countries to frame short term and long-term investment strategies.